Africa Rising : Harnessing the Demographic Dividend - Drummond, Paulo (IMF Working Papers; Working Paper, 2014)
Africa will account for 80 percent of the projected 4 billion increase in the global population by 2100. The accompanying increase in its working age population creates a window of opportunity, which if properly harnessed, can translate into higher growth and yield a demographic dividend. We quantify the potential demographic dividend based on the experience of other regions. The dividend will vary across countries, depending on such factors as the initial working age population as well as the speed and magnitude of demographic transition. It will be critical to ensure that the right supportive policies, including those fostering human capital accumulation and job creation, are in place to translate this opportunity into concrete economic growth.